STUDI HISTOLOGI LIMPA SAPI BALI - Setiasih, Ni Luh Eka; Suwiti, Ni Ketut; Suastika, I Putu; Piraksa, I Wayan; Susari, Ni Nyoman Werdi (Buletin Veteriner Udayana, 2012)
The objective of this study to find out the histological of spleen of bali cattle. Thespleenwere collected from 20 bali cattle in Pesanggaran abattoir, Denpasar and thenevaluated microscopically. Histological findings were assessed by H-E stainpreparations.Microscopically, showed that the spleen of bali cattle consists of capsule,white and red pulp. The capsule composed of connective tissue and smooth muscle withthick of these layer is 24,3 ± 3,7 ?m. The white pulp subdivided into the marginal zone andthe follicle. It is composed of reticulocyte (lymphocytes and macrophages) andreticular fibers. The red pulp composed of arterioles, capillary, and vascular sinusoidswhich are large numbers of erythrocytes, macrophages, dendritic cells, plasma cells andsparse lymphocytes.
Keywords: red pulp, white pulp,spleen, bali cattle